MARTYNAS JANKUS’ ACTIVITY AND ROLE IN LITHUANIAN CULTURAL AND CIVIL MOVEMENT - KAUNAS, DOMAS (Knygotyra, 2015)
Martynas Jankus (1858–1946) is a historical personality. His importance does not diminish with time. The myth of Jankus was created during his life, monuments for him were erected, streets and organisations were named after him. Jankus still makes a significant influence because his interests coincided and coincide with the vital interests of the Lithuanian nation and state. He played an important role in the history of Lithuanian publishing. He established a multifunctional publishing, printing and trading enterprise in Lithuania Minor governed by Prussia. The enterprise was active in 1889−1923. It was mainly oriented towards publishing and production of Lithuanian publications in Latin script prohibited by Tsarist government, and smuggling it to Great Lithuania. It published 400 books and 27 periodicals in the Lithuanian, German, Polish and Byelorussian languages. There were two priorities in Jankus’ activity: commercial and idealist. The first ensured existence of the enterprise and the family; the second allowed him to implement spiritual, educational and political goals. One of the achievements by Jankus’ enterprise was the productivity of his publishing work, a variety of publications as well as their orientation towards secular and polemic issues. This was an important innovation within Lithuanian publishing, formed by Jankus’ orientation towards maturing the national movement, co-operation with the majority of the nation, rapidly evolving social and political powers. Jankus’ historical role is also associated with the innovative experiments in publishing (he tried to produce satirical, daily, and evening periodicals), with expansion of publishing relations between Lithuanian national-revolutionary movement and similar movements in neighbouring countries. A number of Lithuanian young people acquired the qualifications in typography in Jankus’ enterprise. Some of them became initiators and professionals of publishing business in Great Lithuania after the ban on Lithuanian press had been lifted in 1904. At present, the heritage published by Jankus is increasing in value. Almost all books, brochures, periodical and small publications published by him belong to the category of rarities. The search and retrieval of this published heritage is continuing, therefore, we still do not know the precise number of publications produced by Jankus.
Keywords: ...